NUMERICAL ANALYSIS OF CIRCULATION AND DISPERSION OF POLLUTANTS IN VENTILATED BUILDINGS UNDER NON-ISOTHERMAL CONDITIONS - Bianchin, G. P.; Braun, A. L. (Revista de Engenharia Térmica, 2023)
Air quality, thermal comfort and internal circulation in urban areas are closely linked to the promotion of natural ventilation in buildings. In this sense, the main objectives of the present work are to study the effect of internal circulation in buildings with different openings and the phenomenon of pollutant dispersion in naturally ventilated buildings under non-isothermal conditions using a numerical model for incompressible flows with heat and mass transport. For the flow simulation, a semi-implicit Characteristic-Based Split (CBS) scheme is used in the context of the Finite Element Method (FEM), where linear tetrahedral elements are used for spatial discretization. Turbulence is treated using the Large Eddy Simulation (LES) methodology and thermal effects are considered in the momentum balance equation through buoyancy forces, which are calculated taking into account the Boussinesq approximation. Classical examples are analyzed to verify the numerical model proposed here, as well as the forms of natural ventilation and, finally, a numerical investigation is carried out considering the dispersion of pollutants and the thermal effects simultaneously. In addition to ensuring air exchange while maintaining a healthy environment, ventilation helps to disperse pollutants and promotes thermal comfort, both inside the building and in the street canyon, as indicated by results obtained.